The Development of Distance Education in the Russian Federation and the Former Soviet Union - Zawacki-Richter, Olaf; Kourotchkina, Anna (International Review of Research in Open and Distributed Learning, 2012)
Distance education in the present Russian Federation and former Soviet Union has a long tradition that prevails to this day. The majority of students in Russia are enrolled in distance learning programs. The numbers indicate the existence of a well-established system for distance education, of which little is known in Western literature. A review of distance education research in the Anglo-American sphere showed that within the past 10 years not a single article dealing with the Russian system was published. Consequently, within international DE research Russia remains uncharted territory. The following explorative study introduces the educational and tertiary educational system and presents current statistical data while emphasizing the historical perspective to further describe how the distance education system is embedded therein. In order to discuss current practice in this field, one of the biggest higher distance education institutions in Moscow with approximately 110,000 students is used as an example.